[Gas pains ; Dancers ; Straight from the heart [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1990)
Tackles the full supply and the government's energy conservation measures ; discusses the plight of stripteasers ; and an interviews with Jose Mari Chan as a music composer.
Gas pains (16 min.) -- Dancers (15 min.) -- Straight from the heart (17 min.)
VHS.
Keywords: Chan, Jose Mari; Petroleum products -- Prices -- Philippines; Stripteasers -- Social conditions. -- Philippines